Correlation of amikacin concentrations in perilymph and plasma of continuously infused guinea pigs. - Desjardins-Giasson, S (1984)
A commercially available radioimmunoassay kit was modified to enable us to measure, in triplicate, the amikacin concentration in 1 microliter of perilymph fluid. Amikacin levels in plasma and perilymph were measured in guinea pigs after continuous intravenous infusion at four different dosing rates. After a 4-h infusion, a good linear correlation was found between the amikacin concentration in plasma and the dosing rate. Likewise, a significant linear relationship was found between concentrations of amikacin in perilymph and plasma (y = 0.21x + 2.56; r = 0.67; n = 45) after 6 h of infusion. These results suggest nonsaturation kinetics at the concentrations used.